Comparison of del Nido Cardioplegia with Blood Cardioplegia in Coronary Artery Bypass Grafting Combined with Mitral Valve Replacement - Kavala,Ali Aycan (2018)
Abstract Objective: To compare del Nido cardioplegia (DNC) with blood cardioplegia (BC) in coronary artery bypass grafting (CABG) combined with mitral valve replacement. Methods: A 3-year single-center retrospective cohort study was carried out. Subjects who underwent CABG (up to triple bypass) combined with mitral valve replacement were divided into DNC and BC groups. Each group had thirty subjects. Results: Both groups demonstrated similar baseline characteristics, including age, gender, cardiac/non-cardiac comorbidity, and preoperative echocardiographic parameters. Compared with the BC group, the DNC group demonstrated significantly lower cardioplegia volume (BC = 1130.00±194.1 mL, DNC = 884.33±156.8 mL, P=0.001), cardiopulmonary bypass time (DNC = 110.90±12.52 min, BC = 121.70±13.57 min, P=0.002), aortic clamp time (DNC = 91.37±11.58 min, BC = 101.37±13.87 min, P=0.004), and need for intraoperative defibrillation (DNC = 6 events, BC = 21 events, P=0.001). Postoperative creatine kinase-MB levels and troponin levels were significantly lower in the DNC group than in the BC group. Postoperative haemoglobin and haematocrit levels were significantly higher in the DNC group than in the BC group. The intubation period (hours) in intensive care unit (ICU) was significantly small in the BC group (DNC = 8.13±12.21, BC = 6.82±1.57, P=0.037); however, ICU stay, total hospital stay, and postoperative complication rates were not significantly different between them. At pre-discharge echocardiography, the DNC group demonstrated significantly higher ejection fraction rates than the BC group (47.79±5.50 and 45.72±5.86, respectively, P=0.005). Conclusion: DNC presented better intraoperative and postoperative parameters and it is an effective and safe alternative to BC for CABG combined with mitral valve replacement.